Atenuação de harmônicos nos geradores síncronos provenientes das cargas Não Lineares utilizando geradores de indução - Delbone, Edval (2012)
This work demonstrates the theoretical and experimental feasibility of a induction generator to work as an attenuator of the harmonics in main generators of on the electric power system, i.e., the synchronous generators. The induction and synchronous machines were analyzed in physical terms and established mathematical modeling in the frequency domain in order to prove the purpose of the thesis. Computer simulations were also carried out in the time domain and laboratory tests were made to check levels of attenuation of current harmonics (THDi) in accordance with the maximum standardized voltage harmonic distortion (THDv). Furthermore, this work presents a study of technical and economical feasibility of a typical application.